Kinetic and Theoretical Study of Removal Gentian Violet from Aqueous Solution Using Stachy Plant (Baghdad Science Journal, 2023)
The main parameters and methods influencing the removal of Gentian Violet (GV) dye from aqueous media were investigated using a stachy plant in this study. The surface of the stachy plant was determined using FTIR spectra. Adsorption is influenced by the adsorbent's characteristic groups. The research took into account the usual conditions for GV dye adsorption by the stachy plant, such as the impact of contact time. Mass dosage , after 0.3 g the amount of adsorbed dye declines. Study pH and ionic strength, the results obtained showed that at pH 3 the largest adsorption of (GV) was seen, while at pH 9, the lowest adsorption was observed  at 298 K, the adsorption kinetics and equilibrium constants were achieved, and the equilibrium data was fitted using the Langmuir, Freundlich, and Temkin models. The pseudo-first-order and pseudo-second-order kinetic models were used to investigate the adsorption process of gentian violet. The adsorption kinetics was discovered to be governed by a pseudo-second-order kinetic model with a determination coefficient (R2) of 0. 0.9943. Study the theoretical electrostatics of Gentian Violet dye was measured and plotted as a 2D and 3D contour and the program hyperchem-8.07 was used for semi-empirical and molecular mechanic calculations in the gas phase to estimate the total energy.